19 Myocardial perfusion reserve by quantitative perfusion cardiovascular magnetic resonance in dilated cardiomyopathy: association with major adverse cardiovascular events. (28th January 2023) - Javed, Wasim; Goh, Z; Shabi, M; Sharrack, N; Gorecka, M; Levelt, E; Xue, H; Dall'Armellina, E; Kellman, P; Greenwood, JP; Plein, S; Swoboda, PP
Abstract : Introduction: Myocardial perfusion reserve (MPR) is the ratio of global myocardial blood flow (MBF) at stress compared with rest. It is independently associated with major adverse events in coronary artery disease (CAD). Whilst MPR has been shown to be reduced in dilated cardiomyopathy (DCM), its prognostic significance is unclear. Materials and Methods: Patients with a recent diagnosis of heart failure (HF) with left ventricular ejection fraction (LVEF) <50% on echocardiogram were recruited. Exclusion criteria included history of CAD, myocardial infarction (MI), coronary revascularisation or anginal symptoms. They underwent clinical assessment along with quantitative stress-perfusion cardiac magnetic resonance imaging (CMR). Only patients with increased LV end-diastolic volume indexed (LVEDVI), LVEF <50% and no visual evidence of MI or ischaemia on CMR were included. They were followed up for a minimum of 12 months via medical record review for major adverse cardiovascular events (MACE) including cardiovascular death, HF hospitalisation and ventricular arrhythmia. Statistical analysis included receiver operator curve (ROC) analysis to determine optimum MPR cut-off to predict MACE and univariable and multivariable Cox regression. Results: Of 160 patients (median follow up 2.2 years), MACE occurred in 16 (10%) patients (first event n= 12 HF hospitalisation, n=2 ventricular arrhythmia, n=2 cardiovascular death). The optimum cut-off to predict MACE was MPR<2.06, which identified 42 patients. On log-rank testing, patients with MPR<2.06 demonstrated a significantly higher probability of MACE ( figure 1, chi-squared=12.3, P<0.001). Univariate regression showed LVEDVI, LVEF, right ventricular EF (RVEF) and MPR were significantly associated with MACE ( table 1 ). Stress MBF was associated with MACE (HR 0.30, 95% confidence interval (CI) 0.12–0.79, P=0.015) but rest MBF was not (P=0.067). MPR<2.06 was associated with MACE (HR 5.1, 95% CI 1.85–14.04, P=0.002). Stepwise multivariate regression analysis included LVEF, RVEF LVEDVI and MPR<2.06. RVEF was removed from the model and MPR<2.06, when corrected for LVEDVI and LVEF, was still associated with MACE (HR 4.14, 95% CI 1.45 to 11.84, p=0.008). Conclusion: In DCM, reduced MPR was independently associated with increased MACE even after correction for LVEF and LVEDVI. Future studies are needed to reproduce this finding in larger, more varied cohorts and establish whether it can be altered by medical therapy.